Fiber laser welding of NiTi to Ti-6Al-4V. Issue 9 (December 2015) - Miranda, R.; Assunção, E.; Silva, R.; Oliveira, J.; Quintino, L.
Abstract Joining of multimaterials is a major issue for several industrial applications where the combination of individual material properties increases component performance. The objective of this experimental study is to assess the laser weldability of NiTi to Ti-6Al-4V. Dissimilar welds were performed on 1-mm-thick plates with a high-power fiber laser with different heat inputs to control the cooling rate. Fracture was always observed in the weld metal in a solidification cracking phenomena. Scanning electron microscopy with EDS was performed to analyze the fracture surfaces. Solidification cracking was observed in the fusion zone associated to Ti2 Ni formation in two distinct fracture morphologies: brittle transgranular cracking in the Ti2 Ni regions and dimple intergranular failure along the solidification dendrites. Thus, autogeneous welding of these two materials is difficult due to intermetallics formation and filler materials or interlayers are needed to prevent the formation of brittle intermetallics.